Inclusive Teaching Efficacy among Early Childhood Teachers in Zambia - Derick Singogo; Kenneth Kapalu Muzata (MASI Mandiri Edukasi, 2023)
Teachers’ beliefs about their capabilities can impact the quality of implementation of education policies. The inclusive education policy is not an exception in this case. This study explores teachers’ beliefs about their capabilities to teach inclusive early childhood education (ECE)classes under the inclusive education policy. This study has conceptualized this belief as inclusive teaching efficacy. A Qualitative approach with a sample of 15 ECE teachers and two educational officers was interviewed using a semi-structured interview guide. Data were analyzed using interpretive phenomenological analysis (IPA). The major themes from the analysis reveal interesting insights into teachers' beliefs about their capabilities to handle inclusive ECE classes. Their capabilities were influenced by knowledge, exposure, training, and CPDs, among other emerging themes. This study demonstrates the need to prepare teachers for the implementation of policies or policy changes in Education. Most importantly, the study targets teachers’ self-beliefs, which feeds into their motivation and quality implementation of the inclusive education policy. It was recommended that inclusive ECE teachers be exposed to inclusive CPDs and that training institutions beef up curricula to equip teachers with adequate knowledge to manage inclusive ECE learners.